Alternative Therapeutic Options to Antibiotics for the Treatment of Urinary Tract Infections - Loubet, Paul; Ranfaing, Jérémy; Dinh, Aurélien; Dunyach-Remy, Catherine; Bernard, Louis; Bruyère, Franck; Lavigne, Jean-Philippe; Sotto, Albert (Frontiers in Microbiology, 2020)
Urinary tract infections (UTIs) are among the most common bacterial infections in humans, affecting millions of people every year. Uropathogenic Escherichia coli (UPEC) cause the vast majority of UTIs. While antibiotic therapy has historically been very successful in controlling UTIs, the high recurrence rate remains a major problem, and many individuals suffer from chronically recurring UTIs, sometimes requiring long-term prophylactic antibiotic regimens. Furthermore, the global emergence of multi-drug resistant UPEC in the past ten years underlines the need for alternative non-antibiotic therapeutic and preventative strategies against UTIs. In the past few years, the research on non-antibiotic therapeutic options in UTIs has focused on the different steps in the pathogenesis of UTIs, namely urogenital colonization, adherence of uropathogens to uroepithelial cell receptors and invasion. In this review, we discuss vaccines, small compounds, nutraceuticals, immunomodulating agents, probiotics and bacteriophages, highlighting the challenges each of these approaches face. Most of these treatments show interesting but only preliminary results. Lactobacillus-containing products and cranberry products in conjunction with propolis have shown the most robust results to date and appear to be the most promising new alternative to currently used antibiotics. Vaccines and bacteriophages require further research. A deeper understanding of the intricate interplay between these therapies, uropathogens and the host immune system should be the objective of future research. Larger scale clinical trials with standardized treatment regimens, reliable controls and good reproducibility are warranted.